Biblioteca Pública Municipal de Campina Grande-PB: histórias, leitores e leituras - Espíndula, Danielly Vieira Inô (2015)
Spaces created to keep and protect mostly written works produced by men and also to publicize them, libraries always had an uncertain destiny – from its inception to its destruction – and different purposes – from keeping a book as treasure and make it available to the public. In the attempt to recover the history of these institutions we seldom have access to information about who were the readers and how they used this reading space. This is a condition shared by the Municipal Public Library of Campina Grande-PB, founded in 1938 and on which there are few records showing the different stages undergone by the institution over time. On its readers, we have only a few references from the 1950s, when they are to be mentioned in local newspapers texts, but just to have highlighted their absence in the library and their practices rejected. This research - which is a part of a line of studies called History of Reading (CHARTIER, 1996; 2002; 2003; 2012) and understands reading as a social practice - discussed the following questions: what is the history of the Municipal Public Library of Campina Grande-PB (BPMCG) and how this institution was inserted in the cultural context of the city, in three different times - the first years after its foundation, in the 1950s and today? Who are the readers who used the loan service between July / 2008 and May / 2011 and what are their reading practices and their forms of appropriation of the Library? Our overall goal was, therefore, to register the history of the Municipal Library of Campina Grande-PB, at these three mentioned times, and to describe reading stories and practices carried out by its readers in this space or because of it: what they read, how they read, why they read, and how often they read. Contrary to historically constructed speech about BPMCG, where by there are no readers using the institution, we confirmed our thesis that not only these readers exist, but they have their particular way of appropriating the institution and find in it an important support for building their particular reading history as well. The existence of these readers in the library is often denied and their practices are historically rejected, a condition which condemns them to an invisibility which, however, does not correspond to the actual appropriation of reading space by its regulars.